Depression Severity in Electroconvulsive Therapy (ECT) Versus Pharmacotherapy Trials. Issue 1 (March 2015) - Kellner, Charles H.; Kaicher, David C.; Banerjee, Hiya; Knapp, Rebecca G.; Shapiro, Rachael J.; Briggs, Mimi C.; Pasculli, Rosa M.; Popeo, Dennis M.; Ahle, Gabriella M.; Liebman, Lauren S.
Abstract : Objective: We sought to compare the level of severity of depressive symptoms on entry into electroconvulsive therapy (ECT) clinical trials versus pharmacotherapy clinical trials. Data Sources: English-language MEDLINE/PubMed publication databases were searched for ECT literature (search terms: ECT, electroconvulsive therapy, depression, and Hamilton ) for clinical trials in which depressed patients had baseline Hamilton Rating Scale for Depression (HRSD) scores. For comparison, we used a convenience sample of 7 large pharmacotherapy trials in major depression (N = 3677). The search included articles from 1960 to 2011. Study Selection: We included 100 studies that met the following criteria: ECT trial for depression, patients adequately characterized by diagnosis at baseline, and patients rated at baseline by 15-item HRSD (HRSD15), HRSD17, HRSD21, HRSD24, or HRSD28, with mean (SD) and sample size (n) reported. For the comparator pharmacotherapy trials, we chose to use a subset of the studies (excluding one study of minor depression) in the widely publicized meta-analysis of Fournier et al, as well as the STAR*D study and one additional study by Shelton et al. This provided 7 studies of major depression using HRSD17 (total N = 3677). Data Extraction: Data extracted included number of subjects and baseline and final HRSD scores, with mean (SD) values. Results: Of 100 ECT studies, 56 studies (N = 2243) used the HRSD17 version. The mean baseline HRSD17 score in the ECT trials was 27.6, the mean in the pharmacotherapy trials was 21.94, a statistically, and clinically, significant difference. In a subanalysis of the 16 ECT studies that used the HRSD24 version, the mean baseline score was 32.2. Conclusions: This selective literature review confirms that patients who entered ECT clinical trials were more severely ill than those who entered the selected comparator pharmacotherapy trials. Such data highlight the critical role of ECT in the treatment of severe and treatment-resistant mood disorders.